Assessment of compatibilization role of nanoclay in immiscible polystyrene/ethylene–octene copolymer blends via wide‐angle X‐ray scattering, microstructure, rheological analyses, and mechanical properties. Issue 22 (4th December 2019) - Kiani, Fatemeh; Entezam, Mehdi; Khonakdar, Hossein Ali; Jafari, Seyed Hassan; Callsen, Christoph; Altstädt, Volker
ABSTRACT: Polystyrene (PS)/ethylene–octene copolymer (EOC) blends with 80/20 wt % composition containing different amounts (0, 1.0, 2.5, 5.0 and 7.5 wt %) of an organically modified nanoclay were prepared by one‐step melt‐mixing method. Also, the EOC‐rich blends with 80 wt % EOC content loaded with 0 and 5.0 wt % of the nanoclay were prepared under the similar processing conditions. Presence of both PS and EOC chains in between clay layers localized at the interface of the blends could be deduced by X‐ray diffraction analysis, which suggested formation possibility of PS‐EOC physical structures at the blend interface. Transmission electron microscopy results confirmed that clay nanoparticles were mainly localized at the interface of the blends and also partly in the PS and EOC components of the systems. The localization of the nanoclay was also described by the linear viscoelastic melt rheological studies. It is also revealed that nanoclay had stronger interactions with PS than EOC. This is reflected in the higher tensile properties in the PS‐rich system. The analysis of morphology of the developed systems by emulsification curve revealed that the optimum amount of nanoclay to modify PS‐rich blend is 2.5 wt %. At this clay loading, the blend exhibited the highest impact resistance. According to the overall results, suitability of nanoclay was confirmed for compatibilization of the PS/EOC blends. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2020, 137, 48748. Abstract :